Global, regional, and national burden of uterine fibroids in the last 30 years: Estimates from the 1990 to 2019 Global Burden of Disease Study - Cheng, Lin-Can; Li, Hao-Yang; Gong, Qin-Qin; Huang, Cheng-Yang; Zhang, Chao; Yan, Jin-Zhu (Frontiers in Medicine, 2022)
Objective To study specific information on trends in incidence, mortality, disability-adjusted life years (DALY) and the corresponding trends among five sociodemographic index regions, 21 regions, and 204 countries for decision-making, which would enable policymakers to distribute limited resources and devise policies more rationally. Methods Data on uterine fibroids (UNs) from 1990 to 2019, including incidence, mortality, and DALYs, were obtained from the 2019 Global Burden of Disease Study. An estimated annual percentage change (EAPC) was calculated to assess morbidity, mortality, and DALY trends. Results The incident cases of UFs increased from 5,769,658 (95%UI, 7,634,3995–4,274,824) incidences in 1990 to 9,643,336 (95%UI, 7,178,053-12,714,741) incidences in 2017, and the age-standardized incidence rate was steady at 225.67/100,000 persons (95%UI, 167.33–298.87) in 1990 to 241.18/100,000 persons (95%UI, 179,45–318.02) in 2019. The incidence ratio in the high sociodemographic index (SDI) region showed a unimodal distribution, with peaks in 2005. Between 2009 and 2017, the age-standardized death rate of UFs declined globally, especially in low-SDI and low-middle SDI regions. In contrast with 860,619 DALYs (95%UI, 473,067-1,505,289) in 1990, the number of DALYs was 1,378,497 (95%UI, 710,915-2,475,244) in 2019, which had increased significantly, whereas the age-standardized DALY rate decreased expressively with an EAPC of −1.93 (95%CI, from −2.16 to −1.71). Conclusion The global burden of UFs increased between 1990 and 2019, and the incidences and DALYs increased prominently worldwide, while the deaths from UFs had no evident growth. Lower SDI regions carried an incremental burden of UFs, while disease reduction was observed in higher SDI regions. It is high time we paid attention to the underprivileged regional quality of life and health protection.